Shared active site architecture between archaeal PolD and multi-subunit RNA polymerases revealed by X-ray crystallography - Ludovic Sauguet (Nature Portfolio, 2016)
The structures of many DNA polymerases is known, but PolD was a missing piece. Here, the authors report the crystal structure of this protein and use it to connect the DNA replication machinery with the transcription machinery in the same protein family.